CONDUCTING INDEPENDENT WORK IN UZBEK LITERATURE (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2025)
This article explores the methodologies and significance of conducting independent work in the field of Uzbek literature. It emphasizes the importance of fostering students' critical thinking, creativity, and self-management skills through independent study. The article outlines various strategies for effectively organizing independent tasks, including setting clear objectives, utilizing diverse resources, and encouraging collaborative discussions among students. Additionally, it highlights the role of innovative teaching methods and technology in enhancing the learning experience. By implementing these approaches, educators can significantly improve students' engagement and understanding of Uzbek literary works, ultimately contributing to their personal and professional development.